The Effect of Customary Law on The Distribution of Heritage to Indigenous Peoples in Indonesia - Olyvia Rosalia; Firayani; Taupiq (Journal of Adat Recht, 2025)
This study discusses the influence of customary law on the distribution of inheritance within indigenous communities in Indonesia, as well as how customary law is recognized within the national legal system. Indigenous communities possess diverse inheritance systems, such as patrilineal (Batak, Nias), matrilineal (Minangkabau), and bilateral (Javanese, Sundanese) systems, which often differ from the provisions of positive law, such as the Civil Code and the Compilation of Islamic Law. This study employs normative legal research methods with a statutory approach to analyze the regulations governing customary inheritance. The findings indicate that although the state has acknowledged the existence of customary law through Article 18B Paragraph (2) of the 1945 Constitution, Law No. 5 of 1960, and Law No. 6 of 2014, challenges remain in its implementation particularly regarding conflicts with national law and the potential for gender discrimination in certain customary systems. The study concludes by emphasizing the need for harmonization between customary and national law to create a more equitable inheritance system that aligns with the principles of human rights protection.